Hybrid Materials Based on Keggin Phosphotungstate and Bipyridine with Valuable Hydrophobic and Redox Properties - Hidalgo, Gabriel; Devillers, Michel; Gaigneaux, Eric M (Inorganic chemistry, 2022)
A thorough investigation of two novel hybrid materials, namely, (2,2'-Hbpy)3[PW12O40] and (4,4'-H2bpy)1.5[PW12O40]·1.5H2O built from Keggin phosphotungstic acid (PTA) and bipyridine, describes the impact of bipyridine isomers in their formation and physicochemical properties. The hybrids' formation was confirmed by powder X-ray diffraction, while infrared spectroscopy (IR) proved the polyoxometalate (POM) structural preservation. The stoichiometric composition and thermal stability of the hybrids were solved by thermogravimetric analysis-mass spectrometry, which also revealed newly acquired hydrophobic properties. Raman and IR spectroscopies demonstrated that the POM skeleton units in both hybrids were distorted compared to the POM in PTA, which induced a decrease of their reduction potentials as observed by diffuse reflectance ultraviolet-visible spectroscopy (DR-UV-vis). The hybrids' acidity was assessed by ammonia temperature-programmed desorption, which showed no remaining acid sites compared to the strong acidic character of the pristine PTA. The properties of the hybrids were tested in the epoxidation of cyclooctene in the presence of H2O2. The reaction was boosted when the hybrids were pre-activated with H2O2.A thorough investigation of two novel hybrid materials, namely, (2,2'-Hbpy)3[PW12O40] and (4,4'-H2bpy)1.5[PW12O40]·1.5H2O built from Keggin phosphotungstic acid (PTA) and bipyridine, describes the impact of bipyridine isomers in their formation and physicochemical properties. The hybrids' formation was confirmed by powder X-ray diffraction, while infrared spectroscopy (IR) proved the polyoxometalate (POM) structural preservation. The stoichiometric composition and thermal stability of the hybrids were solved by thermogravimetric analysis-mass spectrometry, which also revealed newly acquired hydrophobic properties. Raman and IR spectroscopies demonstrated that the POM skeleton units in both hybrids were distorted compared to the POM in PTA, which induced a decrease of their reduction potentials as observed by diffuse reflectance ultraviolet-visible spectroscopy (DR-UV-vis). The hybrids' acidity was assessed by ammonia temperature-programmed desorption, which showed no remaining acid sites compared to the strong acidic character of the pristine PTA. The properties of the hybrids were tested in the epoxidation of cyclooctene in the presence of H2O2. The reaction was boosted when the hybrids were pre-activated with H2O2.